Cutaneous leishmaniasis caused by members of Leishmania braziliensis complex in Nayarit, State of Mexico - Gustavo Sanchez-Tejeda; Noris Rodríguez; Carlos I Parra; Omar Hernandez-Montes; Douglas C Barker; Amalia Monroy-Ostria (Memorias do Instituto Oswaldo Cruz, 2001)
An epidemiological study was carried out in the northern Mexican state, Nayarit. Fourteen patients with possible cutaneous leishmaniasis skin lesions gave positive Montenegro skin tests. Biopsies were taken from the skin ulcer and analyzed by polymerase chain reaction (PCR) with specific primers for the Leishmania mexicana complex; however all biopsies were not amplified. PCR carried out with specific primers for the L. braziliensis complex resulted in the amplification of all patient DNA. DNA from 12 out of 14 biopsies gave positive amplification with primers species specific for L. (Viannia) braziliensis and hybridized with a species specific L. (V.) braziliensis probe. These results demonstrate the presence in Nayarit of at least two members of the L. braziliensis complex. Most of the cutaneous lesions were caused by L. (V.) braziliensis and two by another species belonging to the L. braziliensis complex. As far as we are aware, this is the first report of L. (V.) braziliensis in Nayarit. The main risk factor associated with the contraction of this disease in Nayarit is attributed to working on coffee plantations.